2016
DOI: 10.1097/md.0000000000003470
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Immune Response to Interferon Gamma Release Assay and Tuberculin Skin Test Among BCG Vaccinated Children in East of Egypt

Abstract: Bacille Calmette-Guérin vaccine (BCG) vaccination is used routinely in most of countries, especially developing one. The efficacy of the BCG vaccination generally decreases with time. The tuberculin skin test (TST) is a most popular diagnostic test for suspicion of tuberculosis (TB) in children till now, but it has many false positives. The interferon-gamma release assay (IGRA) is more specific than TST for detection of childhood TB, as it is more specific to Mycobacterium tuberculosis.Evaluate the interferon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…The pediatric age group in the current study was asymptomatic in 100% of the cases, which is different from other studies [29]. However, there is an assumption that the Bacillus Calmette-Guérin (BCG) vaccine might reduce the clinical presentation of COVID-19 infection in the pediatric age group [20,30] as BCG is an obligatory vaccine in Egypt, including and its booster doses among young children [31,32]. The same results were encountered in a small study coming from upper Egypt, including 36 patients with mild/moderate COVID-19 infection and 30 patients with severe/critical conditions.…”
Section: Discussioncontrasting
confidence: 69%
“…The pediatric age group in the current study was asymptomatic in 100% of the cases, which is different from other studies [29]. However, there is an assumption that the Bacillus Calmette-Guérin (BCG) vaccine might reduce the clinical presentation of COVID-19 infection in the pediatric age group [20,30] as BCG is an obligatory vaccine in Egypt, including and its booster doses among young children [31,32]. The same results were encountered in a small study coming from upper Egypt, including 36 patients with mild/moderate COVID-19 infection and 30 patients with severe/critical conditions.…”
Section: Discussioncontrasting
confidence: 69%
“…After its advent in 1921, the live attenuated BCG vaccine remains the most widely used vaccine until today despite its limitations and highly variable efficacy in providing protection against childhood pulmonary TB. 10 Our results showed that only 76 % of enrolled infants had BCG scar, while the remaining 24% had scar failure versus 17 % (in 100 studied Sudanese infants), and 18 % (in 150 studied Egyptian children) as reported by Kheir et al 11 and Beshir et al 12 respectively, who used the Danish strain of BCG vaccine. It has been reported that scar failure may occur in 10% to 20 % of BCG vaccinated infants and is more common with immunization within 48 hours of life.…”
Section: Discussionsupporting
confidence: 61%
“…In Ghana BCG scar was visible in 89.3% (17) and in Nigeria the BCG scar was visible in 81.5% (18). Absence of BCG scar was reported in Egypt (19) , Korea (20) and West Africa (21), Nigeria (9). Scar failure may be attributed to different factors including the strain of BCG used for vaccination as there are some strains of BCG produced by different manufacturers with no standardized method between them (22), hence the strains may genetically differ (23), and result in different reactivity and immune response that affect protection against TB (22,24).…”
Section: Discussionmentioning
confidence: 94%